Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq - Dronen, Norman O.; Al-Kassar, Nothiala R.; Ali, Atheer H.; Abdulhameed, Mohanad F.; Abdullah, Basim H.; Al-Mayah, Sabeeh H. (Zootaxa, 2017)
A total of 19 white-tailed lapwing, Vanellus leucurus, were collected from Huwazah Marsh, north-eastern Basrah Province, Iraq from February to March and in October, 2011 (collection site #1) and 60 V. leucurus were collected from Al-Hammar Marshes, Thi-Qar Province, southern Iraq from July to November, 2012 (collection site #2), and examined for cyclocoelids. Nineteen Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 from site #1 and 17 specimens from site #2 were fixed with minimal compression for comparisons of morphological characteristics, measurements, morphometric percentages and morphometric ratios commonly used to distinguish species of cyclocoelids. An additional five adult specimens from site #1 were fixed without compression for comparisons. Specimens from site # 1 (n=24) represented only fully-developed, non-senescing adults, while those from site #2 (n=17) could be divided into fully-developed (non-senescing) adults (n=8); younger (smaller, less developed) adults (n=5) and senescing adults (n=4). The following characteristics were relatively consistent, and appeared to be valuable in identifying groups of similar species and distinguishing species in Uvitellina: the presence or absence of the oral sucker; the oral sucker/pharynx width ratio; the posterior extent of the cirrus sac relative to the intestinal bifurcation; the position of the genital pore relative to the pharynx; the position of the testes in the body; the length of the intertesticular space; the length of the posttesticular space; the lateral disposition of the uterine loops; the presence of a posteriorly-directed, tail-like extension off the posterior confluence of the vitelline fields; the posterior extent of the uterine loops relative to the gonads; and the size of fully-developed eggs. It may be beneficial to calculate the percentage that measurements represent relative to the body length to provide insight into the relationship of the size of a structure to increased size of the specimens (growth). Specimens fixed without compression appeared to be less uniform, less symmetrical, shorter, more distorted and the internal details were more difficult to see.